Smart girls forever - Leeson, Robert; Scheffter, Axel illustrator (London, UK: Walker books, 1996)
The smart heroines of these folk tales come from different countries around the world. Natasha from Russia is full of comical fantasies but can still outwit the devil; Yamuna from India has eyes like the sun a mind to match; English Marian ... well, she wants to be an outlaw like Robin Hood!
Juvenile